Importance of the Humanist Dimension in Costa Rican Education Today: an Analysis Based on Nuccio Ordine’s Proposal - Castillo Gómez, Francisco (2026)
This study examines the utilitarian paradigm, as well as the humanist-inspired paradigm, critically analyzing its effects on the integral formation of individuals and pointing out the limitations of the current educational model in Costa Rica. In the first section, a critique of the utilitarian paradigm, which has come to permeate almost all areas of modern life, including education, is developed. This approach places utility and efficiency above other values, prioritizing quantifiable results and immediate practical benefits. The study then examines the fundamental elements of the humanist proposal of Nuccio Ordine, who argues that education must go beyond the utilitarian approach to focus on the integral development of people, fostering values and skills that do not necessarily translate into economic benefits. Ordine proposes that humanism should be a transversal axis in basic education, promoting competencies that nurture reflection, self-knowledge and appreciation of culture. In the last section, we reflect on how Ordine’s humanistic perspective could contribute to strengthen the Costa Rican educational system and mitigate some of its current limitations, proposing an education that not only forms competent professionals, but also upright human beings.